Renaissance architecture - Anderson, Christy (Oxford history of art., 2013)
The Renaissance was a diverse phenomenon, marked by innovation and economic expansion, the rise of powerful rulers, religious reforms, and social change. Encompassing the entire continent, Renaissance Architecture examines the rich variety of buildings that emerged during these seminal centuries of European history. Although marked by the rise of powerful individuals, both patrons and architects, the Renaissance was equally a time of growing group identities and communities - and architecture provided the public face to these new identities . Religious reforms in northern Europe, spurred on by.